2020
DOI: 10.1542/peds.2020-1766
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Critical Care and COVID-19

Abstract: and Zemanate participated in creation of the study concept and data interpretation and were involved in data acquisition and drafting and editing the manuscript; and all authors had final approval of the manuscript, approved the final manuscript as submitted, and agree to be accountable for all aspects of the work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
93
1
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(116 citation statements)
references
References 9 publications
14
93
1
8
Order By: Relevance
“…There are some suggestions that several conditions increase the risk of severe disease in children and include hospitalization, mechanical ventilation, congenital heart disease, neurologic, genetic and metabolic conditions [84][85][86]. Other conditions are related to all ages and include: diabetes mellitus I and II, immunocompromised due to solid organ transplant and other conditions, cerebrovascular accidents, chronic pulmonary disease (e.g., cystic fibrosis, moderate to severe asthma), chronic kidney disease, liver disease, pregnancy, obesity, smocking, sickle cell disease, thalassemia, and hypertension [87].…”
Section: Underlying Conditionsmentioning
confidence: 99%
“…There are some suggestions that several conditions increase the risk of severe disease in children and include hospitalization, mechanical ventilation, congenital heart disease, neurologic, genetic and metabolic conditions [84][85][86]. Other conditions are related to all ages and include: diabetes mellitus I and II, immunocompromised due to solid organ transplant and other conditions, cerebrovascular accidents, chronic pulmonary disease (e.g., cystic fibrosis, moderate to severe asthma), chronic kidney disease, liver disease, pregnancy, obesity, smocking, sickle cell disease, thalassemia, and hypertension [87].…”
Section: Underlying Conditionsmentioning
confidence: 99%
“…To date, few studies have been published on COVID-19 or MIS-C in Latin America. A multicenter study from Chile, Colombia, and other countries reported 17 children with COVID-19, but no case of MIS-C 13 ; another multicenter study in Brazil reported 79 confirmed cases of SARS-CoV-2 infection, of which ten were classified as MIS-C 14 ; and the other two were case series from southeastern Brazil (66 cases, six of MIS-C), 15 and from northern Brazil (11 cases of MIS-C). 16…”
Section: Introductionmentioning
confidence: 99%
“…children less than 19 years old with critical COVID-19 requiring PICU management; findings also demonstrate that rhabdomyolysis is rare 17 . The exact pathogenesis that causes muscle destruction from a viral etiology remains unclear as the presence of a virus in muscle is difficult to demonstrate.…”
Section: Discussionmentioning
confidence: 79%